2022
DOI: 10.1037/neu0000854
|View full text |Cite
|
Sign up to set email alerts
|

Impaired metacognition and reduced neural signals of decision confidence in adults with traumatic brain injury.

Abstract: Objective: Metacognition reflects our capacity to monitor or evaluate other cognitive states as they unfold during task performance, for example, our level of confidence in the veracity of a memory. Impaired metacognition is seen in patients with traumatic brain injury (TBI) and substantially impacts their ability to manage functional difficulties during recovery. Recent evidence suggests that metacognitive representations reflect domain-specific processes (e.g., memory vs. perception) acting jointly with gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Higher amplitudes of this component during decision formation preceded higher confidence ratings. This is consistent with previous studies which found that the CPP scales with both implicit (e.g., statistical) and explicit confidence level (Feuerriegel et al, 2022;Fitzgerald et al, 2022;Gherman & Philiastides, 2015Grogan et al, 2023;Herding et al, 2019;Rausch et al, 2020;Zakrzewski et al, 2019). However, previous studies have focused predominantly on perceptual confidence.…”
Section: Cpp/p3 Is a Reliable And Domain General Predictor Of Confidencesupporting
confidence: 92%
See 2 more Smart Citations
“…Higher amplitudes of this component during decision formation preceded higher confidence ratings. This is consistent with previous studies which found that the CPP scales with both implicit (e.g., statistical) and explicit confidence level (Feuerriegel et al, 2022;Fitzgerald et al, 2022;Gherman & Philiastides, 2015Grogan et al, 2023;Herding et al, 2019;Rausch et al, 2020;Zakrzewski et al, 2019). However, previous studies have focused predominantly on perceptual confidence.…”
Section: Cpp/p3 Is a Reliable And Domain General Predictor Of Confidencesupporting
confidence: 92%
“…Based on the topography and timing of the observed clusters, they possibly represent opposite dipoles of the late portion of the P3/central parietal positivity (CPP) component previously implicated in decision-making and subjective measures of perception including confidence (Azizi et al, 2021;Feuerriegel et al, 2022;Fitzgerald et al, 2022;Gherman & Philiastides, 2015Herding et al, 2019;Lim et al, 2020;Tagliabue et al, 2019). Participants' confidence tended to be higher on trials with stronger late CPP amplitude irrespective of the cognitive domain tested, thus highlighting that the CPP reliably reflects domain-general subjective confidence over and above the external stimulus information (i.e., difficulty) and objective accuracy.…”
Section: Late Stimulus-locked Erp Activity Reliably Predicts Domain-g...mentioning
confidence: 98%
See 1 more Smart Citation